The Process of Digital Pathology and its Application in a Study - Eklund, Lauri (My University, 2022)
Digital pathology saw its advent in the 60’s with the introduction of telepathology and was brought into a brighter spotlight in the late 90’s through the technological breakthrough in histopathological imaging, called whole slide imaging (WSI). With steady growth in interest among experts, the latest breakthrough in WSI happened in 2017, when both the US Food and Drug Administration and the European Union approved the use of WSI systems in primary diagnostics. So far, the adoption of digital pathology has been slower than many expected, but many laboratories around the world are looking to switch into a digital workflow. In this text, I aim to describe the history and the technical basics of digital pathology and WSI, as well as discuss some of its most widely used and promising applications in education, research, telepathology, clinical work, and image analysis. To better illuminate the digital workflow, I describe the use of digital pathology in a study by Anttinen M et al., in which the author of this text participated in the form of digitizing the whole slide images used in the study. With the advancements in digital pathology in the past two decades and with the regulation catching up, wider adoption WSI systems is to be expected. Many advantages can be associated with digital pathology e.g., better results in learning for students, cost reductions in clinical work, and the reduction in pathologists’ workload due to automated image analysis methods.
Keywords: Digital pathology, whole slide imaging